THE ROLE OF DIGITAL INCLUSION IN THE SPREAD OF SOCIAL WELFARE AND RELIGIOUS VALUES - Musfiah Saidah; Yopi Kusmiati; Ade Irmayanti (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2025)
Abstract. Digital inclusion has become critical in ensuring equitable access to information and communication technologies, particularly in disseminating religious values and promoting social welfare. This study explores how digital inclusion through access to internet connectivity, digital devices, and digital literacy supports the spreading of Islamic da'wah messages and welfare related content on popular platforms such as YouTube, Instagram, and TikTok. Each platform offers different features that affect how effectively messages are delivered and received, particularly among diverse and marginalized audiences. Using a quantitative approach with the Digital Action Research method, this study analyzes user engagement metrics such as likes, comments, shares, and views to assess the impact of digital inclusion on the reach and effectiveness of religious and social welfare content. The results show that digital inclusion enhances access to religious information and strengthens social awareness, community participation, and value based education. This research highlights the importance of creating inclusive digital environments to ensure that religious and social messages are accessible, relevant, and impactful for all segments of society. Keyword: Digital inclusion, social welfare, religious values, da’wah, social media. Abstrak. Inklusi digital menjadi faktor penting dalam memastikan akses yang merata terhadap teknologi informasi dan komunikasi, khususnya dalam penyebaran nilai keagamaan dan promosi kesejahteraan sosial. Penelitian ini mengkaji bagaimana inklusi digital melalui akses terhadap koneksi internet, perangkat digital, dan literasi digital mendukung penyebaran pesan dakwah Islam serta konten-konten yang berkaitan dengan kesejahteraan sosial di platform populer seperti YouTube, Instagram, dan TikTok. Setiap platform memiliki fitur yang berbeda yang memengaruhi efektivitas penyampaian dan penerimaan pesan, terutama bagi audiens yang beragam dan rentan. Dengan pendekatan kuantitatif melalui metode Digital Action Research, penelitian ini menganalisis metrik keterlibatan pengguna seperti jumlah suka, komentar, bagikan, dan tayangan untuk menilai dampak inklusi digital terhadap jangkauan dan efektivitas konten keagamaan dan sosial. Hasil penelitian menunjukkan bahwa inklusi digital tidak hanya meningkatkan akses terhadap informasi keagamaan, tetapi juga berperan penting dalam memperkuat kesadaran sosial, partisipasi komunitas, dan pendidikan berbasis nilai. Penelitian ini menekankan pentingnya menciptakan lingkungan digital yang inklusif agar pesan-pesan keagamaan dan sosial dapat diakses, diterima, dan berdampak bagi seluruh lapisan masyarakat. Keyword: Inklusi digital, kesejahteraan sosial, nilai keagamaan, dakwah, media sosial.